Integrating evolving Islamic legal principles with civil forfeiture law to combat digital corruption in Malaysia - Abdul Raof, Nurazlina; Abdul Aziz, Norazlina; Omar, Nadia; Othman, Rozita; Mammoo, Napisah Narikkodan (Journal of Islamic, Social, Economics and Development, 2025)
The recovery of unlawful gains via civil forfeiture is increasingly acknowledged as an effective alternative to criminal enforcement in the fight against corruption and money laundering. Nonetheless, the practice is constrained by the difficulty of satisfying the standard of proof. The technological breakthroughs that generate digital assets, like cryptocurrencies and blockchain, exacerbate the issue. These digital assets' anonymity, pseudonymity, and transnational attributes enable offenders to conceal illicit assets, complicating asset tracing and recovery efforts. Islamic law permits the forfeiture of unlawful gains. Scholars offer insights on the justification for reversing the onus of proof to address the challenges associated with meeting the standard of proof, akin to the principle of presumption. The paper examines the difficulties in recovering unlawful gains from corruption and money laundering under the civil forfeiture law in the Malaysian Anti-Corruption Commission Act 2009 (MACC Act) and the Anti-Money Laundering, Anti-Terrorism Financing And Proceeds of Unlawful Activities Act 2001 (AMLA). It explores how the Islamic legal principle of reversing the onus of proof can be applied to enhance enforcement effectiveness concerning digital assets. It also suggests an alternative mechanism for recovering unlawful corruption assets related to digital transactions. The paper utilises a qualitative study, employing a doctrinal approach and a library-based method, to lay the groundwork for the research. The data were classified into themes and examined through content and thematic analysis. The government and policymakers may need to undertake legal reforms aligned with Islamic legal principles to strengthen the civil forfeiture in recovering unlawful gains associated with corruption and money laundering. The paper’s findings facilitate the revision of quotidian practices and the legislative framework of civil forfeiture in Malaysia.